PERILAKU MENYONTEK PADA SISWA DITINJAU DARI KEPERCAYAAN DIRI DAN STRATEGI COPING - Solagrasia, Kartika (Universitas Sahid Surakarta, 2014)
Cheating behavior is one of education phenomena that often appearing in the teaching learning process. But the teachers and educator are still continues to confuse because they have not managed to find a method to stop habit cheated of the students. One of the factor which influence cheating behavior is the pressure to got good grades in examinations and will be the best achievement. ThisÂ studyÂ aimsÂ toÂ determineÂ theÂ correlationÂ betweenÂ selfÂ confidenceÂ with cheatingÂ behaviorÂ andÂ correlationÂ betweenÂ copingÂ strategyÂ withÂ cheatingÂ behaviorÂ in examinations.Â MeasuringÂ instrumentsÂ wereÂ usedÂ areÂ CheatingÂ BehaviorÂ Scale,Â Self Confidence Scale and Coping Strategy Scale. The population of the research is Surakarta I Christian senior high school students while the number of sample is 60 people, which is obtained through byÂ cluster random sampling technique. The data analyze technique in thisÂ researchÂ useÂ theÂ doubleÂ linierÂ regressionÂ analysisÂ withÂ SPSS forÂ WindowsÂ Release 16,0. The resultsÂ ofÂ data analysisÂ showed thatÂ thereÂ wasÂ notÂ significant correlation betweenÂ selfÂ confidenceÂ withÂ cheatingÂ behaviorÂ inÂ examinationsÂ getÂ obtainedÂ ÏÂ value equalÂ toÂ 0,459Â >Â 0,05.Â SubsequentÂ dataÂ analysisÂ showedÂ thatÂ thereÂ wasÂ aÂ significant correlation between coping strategy with cheating behavior in examinations, proofed to be obtain Ï value equal to 0,000 < 0,05. The result means variable coping strategy covers internal aspect can be become predictor to predict or measure cheating behavior. Keyword : cheating behavior, coping strategy, self confidence